A comparative analysis of macro and micronutrient content in nutraceutical "Asparagus racemosus (Shatavari Roots)" by energy dispersive X-ray fluorescence and ion chromatography - Shalvi Agrawal; Astha Pandey (Wolters Kluwer Medknow Publications, 2022)
Introduction: Shatavari is indeed a highly rejuvenating herb for both males and females, a revitalizing tonic for most of the problems related to hormonal changes and reproductive system and is a commonly used nutraceutical. Macro and micro elemental concentration of the Ayurvedic medicinal plant, Shatavari (Asparagus racemosus), is investigated for the first time in detail, using Energy Dispersive X-Ray Fluorescence (EDXRF) technique and Ion Chromatography with Conductometric Detector (IC-CD). Methods: In the present study, root powders have been analyzed directly by EDXRF, and extracted root samples have been analyzed by IC-CD. The data of standard plant sample has been compared with ten other market samples. Results: The EDXRF results have been given for 20 elements in percentage composition for K, Ca, P, Si, S, Fe, Zn, Mn, Ti, Cu, Ba, Sr, Ni, V, Cr, Os, Ho, Br, Ge, and Rb whereas IC-CD results have been given in ppm level for six essential elements for Li, K, NH4+, Ca, and Na. Discussion: It has been found from the results that there are many essential elements that were absent in some of the commercial samples. Some samples reported very low concentration of one or the other elements that are crucial for its role in human body owing to which the nutraceutical is consumed. Conclusion: The results revealed a significant difference between the standard and the sample drug by both the methods suggesting that there is indiscriminate use of exhausted and adulterated drug in commercially available nutraceuticals. Furthermore, there is a crucial need to standardize such drugs before it reaches consumers.